2011
DOI: 10.6026/97320630006291
|View full text |Cite
|
Sign up to set email alerts
|

Allotment of carbon is responsible for disorders in proteins

Abstract: Sequence stretches in proteins that do not fold into a form are referred as disordered regions. Databases like Disport describe disordered regions in proteins and web servers like PrDOS and DisEMBL, facilitate the prediction of disordered regions. These studies are often based on residue level features. Here, we describe proteins with disordered regions using carbon content and distributions. The distribution pattern for proteins with disordered regions is different from those that do not show disordered regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Allotment of carbon is responsible for disorders in proteins [4]. The carbon distribution analysis in disordered proteins is the focus of this work by taking neurodegenerative protein.…”
Section: Introductionmentioning
confidence: 99%
“…Allotment of carbon is responsible for disorders in proteins [4]. The carbon distribution analysis in disordered proteins is the focus of this work by taking neurodegenerative protein.…”
Section: Introductionmentioning
confidence: 99%
“…These mutants at residue position 30, 33 and 36 were characterized by broadened distribution curve for carbon content with decreased carbon frequency peak thus destabilized protein function in terms of its sweetness. Broadened carbon distribution curve with decreased frequency peak destabilizes the structure and possibly leading to loss of protein functionality [12,14]. Based on carbon distribution analysis on several numbers of proteins, it has previously been reported that at mutation site, a single mutation can alter the protein function [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The residues specifically examined were in position number 29, 30, 31, 33, 36, 41 and 43. In order to elucidate the variation between mutants with increased brazzein sweetness and the mutants with decreased brazzein sweetness, analysis for local carbon density at the mutational sites was done along brazzein protein sequences for the mutants using a protein sequence CARD program for carbon [12,13].The carbon content distribution profile outputs of Carbana and sequence CARD were then plotted for better visualization of results. For the analysis of the carbon distribution profile for brazzein sequences both the wild-type and mutants, the Carbana software available online (www.rajasekaran.net.in/tools/carbana.html) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When there is inadequate carbon point of distribution where alteration can be performed by probe binding at the adjacent site effectively. Accordingly initiatives are done to probe the role of carbon in dealing with other situations like, pattern recognition, 7,8 disorders in protein, 9,10 disease causing 11,12 and mutational role [11][12][13][14][15] when other forces fail to capture the essence of it. When in need one can probe those devisable mechanisms for possible arrangements to continue with carbon value based method of alternative design and action actually taken here.…”
Section: Introductionmentioning
confidence: 99%